Expert Systems in Business and Finance: Issues and Applications. - Denna, Eric L.; Boatsman, James R. (The Accounting Review, 1994)
Abstract Reviews the book `Expert Systems in Business and Finance: Issues and Applications,' by Paul R. Watkins and Lance B. Eliot.